Clinical Audit Of Blood Requisition And Transfusion Practices In Obgyn Surgeries In A Secondary Care Setting - Erum Saleem Khan; Reeta Chanderprakash; Sheikh Irfan; Sana Yousuf (ziauddin University, 2018)
Objective: This study aimed at designing an audit tool for better understanding of pre-operative blood requisition and transfusion practice. These findings may help to provide evidence that an organization is working towards/meeting JCIA quality criteria of Cross match Transfusion ratio of 2:1. Methods: Analysis of data over the first 3 months revealed over ordering of cross matched blood resulting in a high Cross match transfusion ratio. Some strategies were devised including: 1. Use of group and screen instead of routine cross matching.2.listing the major indications for cross matching of blood.3. Preoperative and antenatal anemia correction.4. All time availability of O negative blood. 4. Education of staff and doctors about these strategies. Results: In the next 3 months the number of units cross matched fell moving towards a trend of group n save of blood samples resulting in significant improvement of CT Ratio.This helped us in efficient utilization of this limited resource. Conclusion: Regular audits must be done in order to improve the blood ordering and utilization practice in every hospital setting.The audit tool developed for monitoring of Cross match transfusion ratio in Ob/Gyn surgeries and thereby strategies for improvement of this quality indicator was found very helpful.